A novel releasable wick suture for early intraocular pressure control in Baerveldt tube surgery - Tung T. Hoang; Edward Lo-Cao; Shenouda Girgis; Ridia Lim (African Vision and Eye Health)
Background: Early post-operative intraocular pressure (IOP) control following Baerveldt tube (BVT) implant is critical, especially in cases with advanced glaucoma.